2017
DOI: 10.1016/j.foodchem.2016.12.062
|View full text |Cite
|
Sign up to set email alerts
|

Tetraplex PCR assay involving double gene-sites discriminates beef and buffalo in Malaysian meat curry and burger products

Abstract: Replacement of beef by buffalo and vice versa is frequent in global markets, but their authentication is challenging in processed foods due to the fragmentation of most biomarkers including DNA. The shortening of target sequences through use of two target sites might ameliorate assay reliability because it is highly unlikely that both targets will be lost during food processing. For the first time, we report a tetraplex polymerase chain reaction (PCR) assay targeting two different DNA regions in beef (106 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…32 Literature search revealed that several qPCR methods are available for the identification and quantification of beef and buffalo 33 and beef and pork, 30,34 but no mqPCR systems have been documented for the simultaneous detection and quantification of cattle, buffalo, and porcine materials in the food chain. Recently, we have documented multiplex PCR 35 and PCR-RFLP 12 assays for the simultaneous identification of these materials in the food chain, but those methods are just limited to the qualitative detection; they cannot tell how much adulterants are present in the real-world specimens. Thus, the objective of the present study was to develop and validate a short-amplicon length tetraplex qPCR system that would allow both identification and quantification of cattle, buffalo and porcine derived materials in processed foods such as hotdogs, meatballs, and burgers, which are very popular on all continents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…32 Literature search revealed that several qPCR methods are available for the identification and quantification of beef and buffalo 33 and beef and pork, 30,34 but no mqPCR systems have been documented for the simultaneous detection and quantification of cattle, buffalo, and porcine materials in the food chain. Recently, we have documented multiplex PCR 35 and PCR-RFLP 12 assays for the simultaneous identification of these materials in the food chain, but those methods are just limited to the qualitative detection; they cannot tell how much adulterants are present in the real-world specimens. Thus, the objective of the present study was to develop and validate a short-amplicon length tetraplex qPCR system that would allow both identification and quantification of cattle, buffalo and porcine derived materials in processed foods such as hotdogs, meatballs, and burgers, which are very popular on all continents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To simulate an ordinary canning procedure and steam cooking process, we autoclaved the meat samples at 21 °C and 15 psi pressure for 20 min . The meat samples were exposed to microwave cooking, a fast and modern means of cooking, at 600 and 700 W for 30 min . The treated samples were then stored at −20 °C for DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Technologically processed meat is at the forefront of meat product adulteration due to its complex and heterogeneous composition (Naveena et al., 2017), making it difficult to use simple, morphological, or organoleptic approaches to identify its composition. Meat species in the food chain have been previously identified based on protein markers (Montowska et al., 2014), lipid metabolites (Trivedi et al., 2016), and DNA nucleotides (Guntarti et al., 2017; Hossain, Ali, Hamid, Hossain, et al., 2017). DNA‐based technologies have the advantage of stability, uniformity, and polymorphism (Asing et al., 2016a; Druml et al., 2016) over other methods when detecting meat products.…”
Section: Introductionmentioning
confidence: 99%